HUBUNGAN ANTARA SELF ESTEEM DENGAN PENYESUAIAN DIRI SEBAGAI PERAN IBU RUMAH TANGGA PADA IBU BERHENTI BEKERJA DI JAKARTA - Yuke Riana Devi; Endang Fourianalistyawati (Psibernetika, 2018)
Mother stopped working, and chose to become a housewife as may be necessary to adjust themselves well, such as nurturing and caring for the child, completing household chores well, and socialize with the environment around the house. Adjustment is done well will be associated with the formation of a good self esteem. This study aims to determine the relationship between self-esteem with the adjustment to the role of a housewife mother stopped working in Jakarta. The sampling technique in this research using accidental sampling technique by taking the subject as much as 70 housewives in Jakarta. Data analysis techniques used in this study is the Pearson Product Moment Correlation technique. The results of this study indicate that there is a significant positive relationship between self-esteem with the adjustment to the role of a housewife mother stopped working in Jakarta, (r = 0.608, p = 0.000). It can be said that the higher the mother's self-esteem, the better the ability to adjust himself to be a housewife. Conversely, the lower the mother's self-esteem, the worse the ability to adjust himself to be a housewife. Keywords: Self Esteem, Adjustment, Housewife, Mother Stopped Working